2008
DOI: 10.1089/fpd.2008.0145
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Recovery of Foodborne Viruses from Fresh Produce

Abstract: A large percentage of foodborne outbreaks are caused by viruses, and outbreaks associated with fresh produce have increased over the past decade within the United States. Virus recovery from food is of the utmost importance in determining the cause of viral outbreaks. While there are many experimental studies investigating viruses on fruits and vegetables, there is a lack of standard techniques concerning the initial inoculation and recovery of viruses. This study investigates the efficiency of methodology in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
11
0

Year Published

2009
2009
2016
2016

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(12 citation statements)
references
References 24 publications
1
11
0
Order By: Relevance
“…Similar to our results, it was reported that approximately 1 log unit of the viral infectivity titer is lost during the processing step (31,46). This loss could be due to drying, the elution step, and/or the release of various inactivating/damaging factors from plant tissues during the sample processing steps.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Similar to our results, it was reported that approximately 1 log unit of the viral infectivity titer is lost during the processing step (31,46). This loss could be due to drying, the elution step, and/or the release of various inactivating/damaging factors from plant tissues during the sample processing steps.…”
Section: Discussionsupporting
confidence: 90%
“…Spot inoculation was chosen as the method for viral application because it has been shown to be a more efficient method than immersion for application of virus to leaves (31). Control plants included plants not subjected to any of the three stressors and inoculated with viruses (negative treatment control) and stressed plants inoculated with sterile water (negative virus control).…”
Section: Preparation Of Virusesmentioning
confidence: 99%
“…Samples (leaves and roots) were weighed, cut into small pieces, suspended in elution buffer containing MEM supplemented with 2% fetal bovine serum (18), and homogenized on ice using a polytron homogenizer (Cole-Parmer Instruments) at maximum speed for 1 min. Specifically, for lettuce plants age 4 to 5 weeks, all the leaves and roots were harvested (weight of Ͻ3 g; volume of elution buffer used, 10 to 12 ml).…”
Section: Propagation Of Savmentioning
confidence: 99%
“…Food-borne outbreaks of NoV are commonly caused by shellfish grown in contaminated waters (2) or ready-to-eat food products contaminated by infected food handlers (4,5,7,17,21). Methods for the detection of NoV in foods need to be sensitive due to the low numbers of infectious particles present in foods (15) and the lack of a routine cell culture method for amplifying NoV in the laboratory (3,22).…”
mentioning
confidence: 99%